A Retrospective Comparison of the Management of Recalcitrant Lateral Elbow Tendinosis: Platelet-Rich Plasma Injections versus Surgery. (June 2015) - Ford, Ronald D.; Schmitt, William P.; Lineberry, Kyle; Luce, Paul
Background: The aim of this study is to compare the outcomes of platelet-rich plasma (PRP) injections to surgical release and decortication for lateral elbow tendinosis within a similar patient population. Methods: A retrospective chart review was performed on two groups of patients, receiving either PRP injections ( n =28) or surgery ( n =50). Patient demographics, clinical presentation, pain score, worker's compensation status, and previous steroid injections were recorded. Primary outcomes included pain and symptom improvement, range of motion, return to work, and postoperative complications. Results: Demographics, duration of symptoms, and exam findings were similar between the PRP and surgical patients. There was no significant difference in pain and symptom improvement. Pain improvement was reported in 89.3 % of PRP patients and 84 % of surgical patients, with a reported percent reduction in pain of 61.1 and 55 %, respectively. Symptoms other than pain improved in 85.7 and 88 % of the PRP and surgical patients, respectively. Tenderness to palpation at the lateral epicondyle (64.3 % PRP, 44 % surgical), pain with resisted wrist extension (35.7 % PRP, 30 % surgical), or residual symptoms other than pain (14.3 % PRP, 10 % surgical) were not significantly different between groups at last follow-up. Eighty-two percent of patients in both the PRP and surgical groups returned to work. No complications were reported. Mean follow-up was 315 vs. 352 days for the PRP and surgical groups, respectively. Conclusions: Similar outcomes in pain improvement and return to work may be achievable with either PRP injections or surgery in recalcitrant lateral elbow tendinosis. PRP injections may be a reasonable alternative for patients apprehensive to proceed with surgery or poor surgical candidates.